(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2008)
Accountancy unit is looked is upon as unit that established for the purpose achieve it goals and programmers for unlimited time. Unless otherwise take place such as liquation whether voluntary or mandatory. Thus going concern logic is considered to be the logical foundation witch the familiar accounting principles are based upon. The future of a Company real its financial statues and position and the extent of it ability to face events in future. Hence the success and continuity its activities depend on the extent of the company activity to generate profits. And its ability to retain appropriate liquidity to serve its debts. Therefore financial statements of the company consider to be one of the important tools for all parties or stakeholders involved whether inside or outside the company. The study aim is do investigate the hypothesis external auditor is not responsible for assessing the extent of company s financial failure and its continuity researcher relied upon the review and interference method to achieve the study is objective , through reliance of many research aspects upon results of many applied research in this domain and consulting accountancy published literature too. Researcher also relied upon other aspects of interference approach -literature frame work. The results of this study indicate the following;- 1- The early predicting of the financial failure is considered to be one of the means which can be used to avoid losses accumulation and spread to other sectors of the company. This would help the intervention to solve the failure problem in some companies and find solution to minimize the level of losses. 2- Going concern principle considered to be one familiar accounting principle; while this principle is subject to be under the monitoring and rating of company is External Auditor, thus has to perform some extra test to assure the continuity of the company. 3- Through the review of the auditing standards in the united state , the U.K. ,Australia and the International standards relevant to the responsibility of External Auditor over going concern principle , it has reveled that the External Auditor is not responsible in case he/she issues report without mentioning the continuity , and the company announces its bankruptcy shortly there after . However , these standards force External Auditor to conduct additional auditing only in case if there is doubt or uncertainty in regard to the principle of going concern of the company , and through traditional auditing methods .